Along the Journey River : A Mystery - LaFavor, Carole, 1942-2011 (Book collections on Project MUSE., 2017)
"Several sacred artifacts have gone missing from the Minnesota Red Earth Reservation and the suspect list is continuously growing. While it could be the racists from the bordering town, or a young man struggling with problems at home, or the county coroner and his cronies, the need for answers and apprehending the culprit is amplified when Jed Morriseau, the Tribal Chairman, is murdered. Investigating these mysterious occurrences because of tribal traditions and the honor of her family, Renee LaRoche works to track down the people responsible. But can she maintain her intense investigation as well as her new relationship with Samantha Salisbury, the visiting women's studies professor at the white college nearby? Renee is caught between the traditions of her tribe and efforts to help her chimook lover accept their cultural differences"--